2007
DOI: 10.1007/s10637-007-9082-3
|View full text |Cite
|
Sign up to set email alerts
|

Topical henna for capecitabine induced hand–foot syndrome

Abstract: Capecitabine is a chemotherapeutic drug for use in cancers. Hand-foot syndrome (HFS) is side effect of capecitabine which can lead the cessation of the therapy or dose reduction. Henna (Lawsonia inermis) is a traditionally used plant of Middle-East that is applied on hands and feet. Some of cancer patients in capecitabine treatment who developed HFS, we recommended to apply henna. In these patients, six patients were grade 3 HFS and four were grade 2 HFS. Complete response (CR) were seen in four of grade 3 HFS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 13 publications
(15 reference statements)
0
18
0
2
Order By: Relevance
“…Therefore, the applied intervention was effective and prevented redness in sacrum and eventually pressure ulcer, especially stage 1. Yucel et al evaluated the effect of henna on handfoot syndrome caused by capecitabine and henna, due to its anti-inflammatory, analgesic and antipyretic effects, it could have a good therapeutic effect on reduction of this syndrome without the need to reduce drug dosage (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the applied intervention was effective and prevented redness in sacrum and eventually pressure ulcer, especially stage 1. Yucel et al evaluated the effect of henna on handfoot syndrome caused by capecitabine and henna, due to its anti-inflammatory, analgesic and antipyretic effects, it could have a good therapeutic effect on reduction of this syndrome without the need to reduce drug dosage (19).…”
Section: Discussionmentioning
confidence: 99%
“…The current study aimed to evaluate the effect of henna on prevention of pressure ulcers considering the history of henna consumption and also its various pharmacologic effects including antibacterial, antifungal, antiviral, antimicrobial, anti-parasitic (20)(21)(22), analgesic, antiinflammatory, antipyretic (19,20,23), immune stimulus, anti-skin diseases, antioxidant, anti-tuberculosis, (20) and lack of scientific researches regarding its effect on preventing pressure ulcers.…”
Section: Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, authors have suggested the implementation of the effective Henna use for preventing and treating diabetic foot problems (Mutluoğlu and Uzun, 2009). Case reports from Turkey have documented the effective use of Henna for treating hand-foot ulcers secondary to capecitabine [a drug used for cancer treatment] use (Yucel and Guzin, 2008). Authors have argued that Henna can form a three month-lasting protective layer capable of shielding from microbial invasion (Mutluoğlu and Uzun, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Do innych leków profilaktycznych należą witamina E podawana doustnie oraz amifostyna podawana dożylnie (lek o działaniu cytoprotekcyjnym podawany w trakcie radio-lub chemioterapii). W pojedynczych doniesieniach kazuistycznych proponowane są różne środki miejscowe: inhibitory cyklogenazy 2 (COX-2), 99-procentowy dwumetylosulfotlenek (DMSO), gaziki nasączone nikotyną [33] oraz henna, używana na Wschodzie jako preparat do dekoracji dłoni oraz stóp i zalecana profilaktycznie przez ośrodek onkologiczny w Turcji [45].…”
Section: Zmiany Toksyczne W Obrębie Dłoni I Stópunclassified